Contents of antioxidant A, E, C vitamins, Malondialdehyde (MDA), and Aminotranspherases (ALT, AST) in serum professional football managers during derby matches - Devecioglu, Sebahahattin (Drunpp-Sarajevo, 2012)
Aim: Mental situations are known to induce oxidative stress in individuals subjected to intense psychological conditions. We investigated the serum Antioxidant Vitamins, Retinol (vitamin A), alpha-tocopherol (vitamin E) and ascorbic acid (vitamin C), Malondialdehyde (MDA), alanine transaminase (ALT) and aspartate transaminase (AST) levels of Professional Football Managers during Derby Matches in the 2009-2010 season of the 2nd division of the Turkish professional soccer league in the two neighboring provinces matches (Elazig Football Club-Malatya Football Club), which is described as a derby match. Method: The serum samples of twenty club managers of Elazig Football Club were evaluated for study. Changes in biochemical indices of oxidative damage and enzyme markers of stress were examined during a competitive football season. The main findings of the present study were that the serum Malondialdehyde and blood ALT and AST levels of this group of managers displayed differences at home and displacement. Results: The participants in the two matches went through a period of heavy mental stress. In mean average values and statistical results, they showed changes in their serum MDA, ALT and AST concentrations. Conclusion: In conclusion, the excessive excitement and stress can be effective on professional football manager during derby matches. The results of this study indicated that match stress affects the managers physiologically.
Keywords: Football Manager; Vitamin; Malondialdehyde; Aminotransferase; Oxidative Stress; Psychological stress